Preoperative exposure to anti-tumor necrosis factor therapy in ulcerative colitis patients undergoing ileal pouch-anal anastomosis (IPAA) is not associated with histological fibrosis: A case control study. (May 2019) - Zittan, Eran; Muir, Jennifer; Milgrom, Raquel; Berns, Marc; Gralnek, Ian M.; Cohen, Zane; Riddell, Robert; Silverberg, Mark S.
Abstract: Background: We sought to determine whether preoperative exposure to anti-TNF therapy affects objective histological measures of fibrosis in the colorectum. Methods: Ulcerative colitis (UC) patients who received infliximab as maintenance therapy pre IPAA surgery were identified and compared to anti-TNF-naïve matched controls by age, sex, BMI, disease duration, albumin levels, and post-operative leak outcome. Hematoxylin and eosin- (H&E) and trichrome-stained slides from the most distal, well-oriented, full-thickness section of colorectum from each patient's total colectomy specimen were evaluated. Blinded histopathological assessment of the degree of fibrosis was performed using a semi-quantitative pictorial scale. Results: Histological fibrosis in 65 patients from the therapy group was compared to 65 patients from the matched control group. There were no statistically significant differences in the degree of fibrosis observed in any of the bowel layers. In the lamina propria, 29% of the control group and 28% of the treatment group had fibrosis scores ≥3. Fibrosis scores were higher in the submucosa, with both groups having 66% of patients showing scores ≥3. Similarly, in the region above the muscularis propria, 77% of the control group and 80% of the treatment group had fibrosis scores ≥3. In the subserosa, fibrosis scores were lower, with 25% of the control group and 32% of the treatment group having fibrosis scores ≥3. Conclusion: Resection specimens from UC patients treated with maintenance anti-TNF therapy who underwent IPAA surgery showed no significant differences in the degree of histologic fibrosis in any of the bowel layers compared to a matched control group. Highlights: This is the first study to evaluate the effects of anti-TNF on histopathology of resected colorectal specimens from subjects with UC undergoing IPAA. We found that UC patients treated with maintenance anti-TNF therapy showed no significant differences in the degree of histologic fibrosis. We showed that maintenance anti-TNF prior to IPAA surgery does not increase the risk of anastomosis failure or IPAA leak due to colonic fibrosis.